Hubungan antara Pemahaman Ibu Nifas Tentang Perawatan Payudara Terhadap Kelancaran ASI - Fatmawaty Amir Tangke; Riska Mila Valentina (JURNAL KESEHATAN TERAPAN, 2026)
Breast care during the postpartum period plays an important role in preparing the breasts for breastfeeding. This care includes maintaining breast hygiene, both before and after breastfeeding, as well as caring for the nipples to prevent injury or chafing during breastfeeding. Exclusively breastfeeding a baby from birth to a certain age is an important effort to support optimal growth and development. This study was conducted at PMB Puruk Cahu with 40 respondents using a quantitative analytical design with a cross-sectional approach. The results of the study show that postpartum mothers with a good understanding of breast care mostly have smooth milk production, with a Chi-Square statistical test result of p = 0.002 < 0.05.